2014
DOI: 10.1073/pnas.1303559111
|View full text |Cite
|
Sign up to set email alerts
|

ARF1–GTP regulates Asrij to provide endocytic control of Drosophila blood cell homeostasis

Abstract: Significance Ras small GTPases including ARFs act as molecular switches to modulate signaling pathways involved in hematopoiesis. Decreased guanine nucleotide exchange factor activity or increased GTPase-activating protein activation are associated with many leukemias, myelodysplastic syndromes, and myeloproliferative disorders. Drosophila is a good model to address questions related to aberrant hematopoiesis. Using Drosophila genetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 40 publications
(55 reference statements)
9
86
0
Order By: Relevance
“…Upon depletion of ARF1-Asrij endosomal axis we find increased ubiquitination of Cactus, a negative regulator of the Toll pathway, in both hemocytes as well as fat bodies. This suggests non-autonomous regulation of signals by the ARF1-Asrij axis, which is in agreement with our earlier model of signalling through this route (Khadilkar et al 27 ). Thus the endosomal axis may systemically control the sorting and thereby degradation of Cactus, which in turn promotes the nuclear translocation of Toll effector, Dorsal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Upon depletion of ARF1-Asrij endosomal axis we find increased ubiquitination of Cactus, a negative regulator of the Toll pathway, in both hemocytes as well as fat bodies. This suggests non-autonomous regulation of signals by the ARF1-Asrij axis, which is in agreement with our earlier model of signalling through this route (Khadilkar et al 27 ). Thus the endosomal axis may systemically control the sorting and thereby degradation of Cactus, which in turn promotes the nuclear translocation of Toll effector, Dorsal.…”
Section: Discussionsupporting
confidence: 93%
“…Following fly lines were used: arj 9 / arj 9 , UAS-asrij (Kulkarni, Khadilkar et al 30 ), Rel E20 , Black cells ( Bc 1 / CyO ), Hop Tum1 , Imd 1 (NCBS stock centre), Pvr/Cyo (Pernille Rorth, Denmark), Gal4 driver lines e33cGAL4 (Kathryn Anderson, NY, USA), HmlGal4 , UASGFP (Tina Mukherjee, inStem), UAS-arf1 (Khadilkar et al . 27 ), btl-Gal4 (Arjun Guha, inStem), UASarf1rnai (VDRC), GFP reporter flies for Toll and Imd pathway (David Ferrandon, France).…”
Section: Methodsmentioning
confidence: 99%
“…It was thus proposed that the PSC provides a microenvironment that supports hematopoietic progenitor maintenance in the LG (10,11). In line with this model, increasing or decreasing PSC size/activity can, respectively, impede or promote hemocyte differentiation (11,(13)(14)(15)(16)(17)(18)(19). However, differentiated hemocytes are frequently observed close to the PSC, and it is unclear how progenitor fate is maintained in the posterior lobes, which are far apart and physically separated from the PSC.…”
mentioning
confidence: 96%
“…Elucidating mechanisms that can integrate the varying inputs received at the cellular level and orchestrate the outcome will be key to generating tools that allow control of the system. Several recent studies highlight the importance of unique signal generation and regulation in cellular organelles, such as endosomes, in a variety of cell types [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Endosomal regulation is a potent mechanism to integrate and modulate signals in Drosophila hematopoiesis 27,28 . We recently showed that the GTP bound form of the ubiquitous endosomal protein ADP Ribosylation Factor 1 (ARF1-GTP), interacts with and regulates the hemocytespecific endosomal protein Asrij to integrate and modulate multiple signaling pathways required to maintain blood cell homeostasis, including the JAK/STAT and Notch pathways and Pvr and Insulin signaling 26,29 . Depletion of ARF1 or Asrij leads to increased circulating and differential hemocyte counts.…”
Section: Introductionmentioning
confidence: 99%